Understanding the landscape of mathematics teachers’ professional development in south africa: A review of literature - Jita, Loyiso Currel; Badmus, Olalekan Taofeek (Prometeica (Mar del Plata), 2025)
Profession development is essential in standardising the quality of teaching across subject areas and impacting learning in more meaningful ways. In South Africa, students’ achievement in mathematics remains abysmal for decades, evident from the National Senior Certificate examinations and allied global reports. Extensive literature adduced several reasons for the anomaly experienced. Evolving mathematics teachers’ practices owing to low achievement justifies among other reasons for professional development. Extensive studies and trainings on professional development of mathematics teachers are available to date with implication on teachers’ practices to alleviate the existing milieu. This study seeks to aggregate literature on mathematics teachers’ professional development with a view to understand the landscape for impending effort by Education Training and Development Practices Sector Education and Training Authority [ETDP SETA]. This literature review exposes comparatively areas of need and improvement in professional development effort. An understanding of this landscape is a pilot study expected to guide on preparation and instrumentation on areas of professional development for mathematics teachers in South Africa. From the review, we observed absence of empirical data in our context comparing the two models of initial teacher education programme. There is an agreement in the literature to direct professional development to content and pedagogy.  Hence, the need for further studies which critically analysed these two areas through the framework of mathematics knowledge for teaching as against the general PCK. O desenvolvimento profissional é essencial para padronizar a qualidade do ensino em todas as áreas disciplinares e impactar a aprendizagem de maneiras mais significativas. Na África do Sul, o desempenho dos alunos em matemática permanece péssimo durante décadas, como é evidente nos exames do Certificado Nacional Sénior e nos relatórios globais aliados. Extensa literatura apresentou diversas razões para a anomalia vivenciada. A evolução das práticas dos professores de matemática devido ao baixo desempenho justifica, entre outras razões, o desenvolvimento profissional. Até à data, estão disponíveis estudos e formações extensivos sobre o desenvolvimento profissional de professores de matemática, com implicações nas práticas dos professores para aliviar o ambiente existente. Este estudo procura agregar literatura sobre o desenvolvimento profissional de professores de matemática com o objetivo de compreender o cenário para o esforço iminente da Autoridade de Educação e Formação do Setor de Práticas de Treinamento e Desenvolvimento Educacional [ETDP SETA]. Esta revisão da literatura expõe comparativamente áreas de necessidade e melhoria no esforço de desenvolvimento profissional. A compreensão deste panorama é um estudo piloto que deverá orientar a preparação e instrumentação em áreas de desenvolvimento profissional para professores de matemática na África do Sul. A partir da revisão, observamos ausência de dados empíricos em nosso contexto comparando os dois modelos de programa de formação inicial de professores. Há um acordo na literatura para direcionar o desenvolvimento profissional para o conteúdo e a pedagogia. Daí a necessidade de mais estudos que analisem criticamente essas duas áreas através do referencial do conhecimento matemático para o ensino em contraposição ao PCK geral. El desarrollo profesional es esencial para estandarizar la calidad de la enseñanza en todas las áreas temáticas e impactar el aprendizaje de maneras más significativas. En Sudáfrica, el rendimiento de los estudiantes en matemáticas sigue siendo abismal durante décadas, como lo demuestran los exámenes del National Senior Certificate y los informes globales aliados. Una extensa literatura aduce varias razones para la anomalía experimentada. La evolución de las prácticas de los profesores de matemáticas debido al bajo rendimiento justifica, entre otras razones, el desarrollo profesional. Hasta la fecha, se encuentran disponibles amplios estudios y capacitaciones sobre el desarrollo profesional de los profesores de matemáticas con implicaciones en las prácticas docentes para aliviar el entorno existente. Este estudio busca agregar literatura sobre el desarrollo profesional de los profesores de matemáticas con miras a comprender el panorama del esfuerzo inminente de la Autoridad de Educación y Capacitación del Sector de Prácticas de Desarrollo y Capacitación Educativa [ETDP SETA]. Esta revisión de la literatura expone comparativamente áreas de necesidad y mejora en el esfuerzo de desarrollo profesional. La comprensión de este panorama es un estudio piloto que se espera oriente sobre la preparación y la instrumentación en áreas de desarrollo profesional para profesores de matemáticas en Sudáfrica. A partir de la revisión, observamos ausencia de datos empíricos en nuestro contexto que comparen los dos modelos de programa de formación inicial docente. Existe un acuerdo en la literatura para dirigir el desarrollo profesional al contenido y la pedagogía. De ahí la necesidad de realizar más estudios que analicen críticamente estas dos áreas a través del marco del conocimiento matemático para la enseñanza frente al PCK general.